In Silico Analysis of Bioactive Compounds in Red Betel Leaves to Glutathion Peroxidase Activity - Mutmainnah Agustiawan Umar; Mega Safithri; Rahadian Pratama (Indonesian Journal of Applied Research (IJAR), 2022)
Glutathione peroxidase (GPx) is one of the antioxidants that acts as a protector of organisms from oxidative stress. Several compounds in certain plants have been shown to increase GPx activity. Red betel leaves are known to contain antioxidant compounds that have the potential to increase GPx activity. This study aims to see the potential of red betel compound as an activator of the enzyme glutathione peroxidase. As many as 44 red betel leaves active compounds which were tested by in silico method started with receptor and ligand preparation, followed by grid box determination, then proceeded to virtual screening and molecular docking. The virtual screening stage eliminated 7 compounds and in Lipinski test stage there were 2 compounds that were eliminated, also the AdmetSAR test eliminated 21 sompunds, so that there were 14 compounds continued to the file preparation stage, molecular docking and analysis of ligand-receptor interactions. The parameters of affinity energy and percentage of binding site similarity (%BSS) used in the molecular docking analysis showed that there are several compounds that have the potential as antioxidant compounds by increasing the performance of the glutathione peroxidase enzyme, the best compound identified is guanidine tartrate with an affinity energy of -4.8 Kcal/mol and BSS percentage of 62.5%, this compound is also considered safe to be consumed based on its physicochemical and toxicity test.